How to write a term paper - Aquino, Gaudencio V.; Aquino, Marvin B. (Mandaluyong City, Philippines : National Book Store, 2005)
The term paper, which is also referred to by some authors as "the library research paper," is an academic requirement for college undergraduates and sometimes secondary-school students. A term paper is intended for submission to the instructor usually at or before the end of a term or period of time, such as semester, a trimester, summer session, or an academic year. The gathering of data or information for the term paper is done, for most the part, through library research.
1. The Meaning of research -- 2. Educational dividends derived from working on a term paper -- 3. The Writing of a term paper requires hard work but it can be fun -- 4. Demands on the researcher -- 5. Finding and limiting a subject -- 6. Using the library -- 7. The Working bibliography -- 8. Evaluating sources -- 9. Note-taking and making an outline -- 10. Direct quotations and the paraphrase -- 11. Footnote usage and the final bibliography -- 12. Writing the paper.
Includes bibliographical references.
Keywords: RESEARCH WRITING